2007
DOI: 10.1007/s11064-007-9380-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Antioxidant System Alterations in an Astrocytoma Cell Line Challenged with Mitochondrial DNA Deletion

Abstract: Oxidative stress can induce mitochondrial dysfunction, mitochondrial DNA (mtDNA) depletion, and neurodegeneration, although the underlying mechanisms are poorly understood. The major mitochondrial antioxidant system that protects cells consists of manganese superoxide dismutase (MnSOD), glutathione peroxidase (GPx) and glutathione (GSH). To investigate the putative adaptive changes in antioxidant enzyme protein expression and targeting to mitochondria as mtDNA depletion occurs, we progressively depleted U87 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…1B-D). There is evidence that, in U o cells with a complete shutdown of the electron transport chain, the decreased level of reactive oxygen species resulted in a down-regulation of the manganese superoxide dismutase, glutathione, and glutathione peroxidase, an important intracellular antioxidant pool (31). As such, compared with wild-type cells, U o cells are more susceptible to oxidative stress and expressed in a higher bystander mutagenesis as shown in the present studies.…”
Section: Discussionsupporting
confidence: 68%
“…1B-D). There is evidence that, in U o cells with a complete shutdown of the electron transport chain, the decreased level of reactive oxygen species resulted in a down-regulation of the manganese superoxide dismutase, glutathione, and glutathione peroxidase, an important intracellular antioxidant pool (31). As such, compared with wild-type cells, U o cells are more susceptible to oxidative stress and expressed in a higher bystander mutagenesis as shown in the present studies.…”
Section: Discussionsupporting
confidence: 68%
“…Oxidative stress generation has been known to be involved in MeHg-induced cytotoxicity at low dose exposure (0.05 mg/kg/day) in neuronal mice [21]. It is well known that O 2 − is converted to H 2 O 2 and O 2 through the enzyme activity of superoxide dismutase (SOD) in astrocytoma cells under the oxidative stress [23]. Thus, our findings suggest that the increased level of intracellular H 2 O 2 but not O 2 may involve the dismutation from O 2 − to H 2 O 2 and O 2 through SOD under lowlevel exposure of MeHg.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have also shown that depletion of mitochondrial DNA results in decrease in GSH and alterations of antioxidant enzymes [40]. Moreover, GSH depletion and resultant oxidative stress and apoptosis has been studied [4143].…”
Section: Discussionmentioning
confidence: 99%